Determinants of China’s GDP Growth: An Empirical Analysis of Macroeconomic Variable - I. Ali; A. Jonas (Управленческие науки)
This study examines the impact of foreign direct investment (FDI), trade, and various macroeconomic factors on GDP growth in China over the period 1982–2022. By Employing the Autoregressive Distributed Lag (ARDL) model, the research investigates the dynamic interplay between GDP growth and fifteen independent variables, including FDI, exports, trade, total debt, and real interest rates. The Augmented Dickey-Fuller (ADF) test confirms the stationarity of the data at first difference. The ARDL model results indicate significant long-term impacts of some variables, particularly the current account balance, exports, and merchandise trade. Short-run dynamics revealed that increased FDI and real interest rates positively affect GDP growth, while increased debt, exports, and final consumption have negative effects. The ARDL bounds test confirms a long-run relationship among the variables. Diagnostic checks show no issues with normality, heteroskedasticity, or serial correlation. This comprehensive analysis provides valuable evidence for policymakers to formulate effective economic policies, promoting sustained growth and stability in China’s rapidly evolving economy.